Association of LOXL1 polymorphisms with pseudoexfoliation in the Chinese - Lee, Kelvin Y.C. (Molecular Vision, 2009)
PURPOSE: Single nucleotide polymorphisms (SNPs) within the lysyl oxidase like-1 gene (LOXL1; rs1048661 and rs3825942) were found to confer risk to pseudoexfoliation glaucoma (XFG) through the pseudoexfoliation syndrome (XFS) in Nordic, Caucasian, and two Asiatic populations (Indian and Japanese). The prevalence (0.2%–0.7%) of XFS in the Chinese is considerably lower compared to Nordic populations. The aim of this study was to determine the association of LOXL1 in Chinese subjects with XFS/XFG. METHODS: Chinese subjects with clinically diagnosed XFS/XFG and normal controls were recruited. Genomic DNA was extracted, and the two LOXL1 SNPs (rs1048661 and rs3825942) were genotyped by bidirectional sequencing. Allele and genotype frequencies were compared between cases and unrelated controls using PLINK. Linkage disequilibrium (LD) calculations and haplotype association analysis were done using the Haploview package and WHAP package, respectively. RESULTS: Sixty-two Chinese patients (17 XFG and 45 XFS) and 171 Chinese controls were studied. The G allele of LOXL1 SNP rs3825942 was moderately associated (OR=10.97, p=0.0018) with pseudoxfoliation in the Chinese. The frequency of the G allele of rs1048661 was not significantly different in cases compared to controls (p=0.142) in the allelic association test. However, the genotype test showed marginal association for rs1048661 (p=0.030). Only three haplotypes were observed (T-G, G-G, and G-A) with G-G as a risk haplotype (p=0.0034) and G-A as a protective haplotype (p=0.00039). T-G, which was a risk haplotype in the Japanese, was not associated with XFG in the Chinese (p=0.124). CONCLUSIONS: Polymorphisms in LOXL1 confer risk to XFS/XFG in the Chinese. The lower incidence of XFS compared to other populations suggests additional genetic or environmental factors to have a major influence on the phenotypic expression of XFS in the Chinese. The G allele of rs3825942 has been shown to be associated with XFS/XFG in all populations studied to date.